2021
DOI: 10.1590/0102-311x00028720
|View full text |Cite
|
Sign up to set email alerts
|

Public spaces and physical activity in adults: insights from a mixed-methods study

Abstract: Public spaces could promote health equity by providing a place for people to engage in physical activity. Whereas most studies show a positive association between public spaces and physical activity, there are still mixed results, especially in low- and middle-income countries. The objectives of this mixed-methods study were: (i) to assess the quantitative association between access to public spaces and physical activity; (ii) to assess the modification of the association by public spaces quality, area-level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
6
1
1
Order By: Relevance
“…However, it was found to be significant in the case of markets and mosques (Table 3). Previous research has shown that accessibility does not have a significant relationship with community visits to parks [11]. However, the survey results of this study show that some park visitors do not consider accessibility at all when visiting City Park 1.…”
Section: Accessibilitycontrasting
confidence: 70%
See 1 more Smart Citation
“…However, it was found to be significant in the case of markets and mosques (Table 3). Previous research has shown that accessibility does not have a significant relationship with community visits to parks [11]. However, the survey results of this study show that some park visitors do not consider accessibility at all when visiting City Park 1.…”
Section: Accessibilitycontrasting
confidence: 70%
“…This means that visitors who consider the number of activities in public spaces also consider the completeness of the supporting facilities in them. This is also supported by previous research which explains that the number and type of facilities in a public space can significantly influence the high number of community visits and activities carried out in it [11]. Thus, public space must be supported by complete supporting facilities so that it can accommodate various kinds of activities and attract the interest of gated and non-gated residents in BSD to carry out activities in public spaces.…”
Section: Conveniencesupporting
confidence: 62%
“…Visto que a maioria dos estudos mostra uma associação positiva entre espaços públicos e atividade física. [20][21] As limitações de generalização dos dados, de fontes secundárias, também decorrem de que todas as informações obtidas são autorreferidas em entrevista telefônica e os indivíduos que não possuem uma linha telefônica fixa e não são residentes das capitais de Estados brasileiros não são incluídos no estudo. Entretanto, isso é amenizado por meio da utilização de fatores de ponderação dos dados, que buscam calcular os percentuais, considerando as diferenças nas variáveis demográficas da amostra do VIGITEL em relação às características da população total, com a pósestratificação.…”
Section: Os Resultados Dounclassified
“…Our study is by far the largest and the first multicountry study on PA and comorbid anxiety/depression from LMICs, where frontline treatments for depression and anxiety (e.g., antidepressants, psychotherapy) are generally limited ( World Health Organization, 2013 ). Furthermore, in LMICs, there is a high rate of out-of-pocket expenditures ( Van Doorslaer et al, 2007 ), and a lack of access to easily accessible, low-cost, attractive, and safe PA facilities in- and outdoors ( Bojorquez et al, 2021 ; Vancampfort et al, 2019 ). There has been a number of randomized controlled trials (RCTs) examining the effect of PA on mental health outcomes ( Firth et al, 2020 ) and the majority were restricted to depression ( Kruisdijk et al, 2019 ; Lewis et al, 2014 ; Ström et al, 2013 ) and anxiety ( Powers et al, 2015 ; Rosenbaum et al, 2015 ) alone.…”
Section: Discussionmentioning
confidence: 99%